NBS Framework for Agricultural Landscapes - Simelton, Elisabeth; Carew-Reid, Jeremy; Coulier, Miguel; Damen, Beau; Howell, John; Pottinger-Glass, Chloe; Tran, Hung Viet; Van Der Meiren, Marlies (Frontiers in Environmental Science, 2021)
Entering the UN Decade on Ecosystem Restoration, interventions referred to as nature-based solutions (NBS) are at the forefront of the sustainability discourse. While applied in urban, natural forest or wetland ecosystems, they are underutilized in agricultural landscapes. This paper presents a technical framework to characterise NBS in agricultural systems. NBS in the agriculture sector is proposed as “the use of natural processes or elements to, over various temporal and spatial scales, improve ecosystem functions of environments and landscapes affected by agricultural practices, and enhance livelihoods and other social and cultural functions”. The framework emerges from a review of 188 peer-reviewed articles on NBS and green infrastructure published between 2015-2019 and three international expert consultations organized in 2019-2020. The framework establishes four essential functions for NBS in agriculture: (1) Sustainable practices – with a focus on production; (2) Green Infrastructure - mainly for engineering purposes such as water and soil, and slope stabilization; (3) Amelioration – for restoration of conditions for plants, water, soil or air and climate change mitigation; and (4) Conservation – focusing on biodiversity and ecosystem connectivity. The framework connects the conventional divide between production and conservation to add functionality, purpose and scale in project design. The review confirmed limited evidence of NBS in agricultural systems particularly in developing country contexts, although specific technologies feature under other labels. Consultations indicated that wider adoption will require a phased approach to generate evidence, while integrating NBS in national and local policies and agricultural development strategies. The paper concludes with recommended actions required to facilitate such processes.